Interlibrary loan - Wolfe, Gene (Wolfe, Gene. Borrowed Man Series, 2020)
A sequel to "A Borrowed Man" is set in a future world of artificial intelligence where a clone is loaned out to a little girl before discovering that his original self, a mystery writer, is still alive.